Computational exploration of Picrasma quassioides compounds as CviR-mediated quorum sensing inhibitors against Chromobacterium violaceum - Revanasiddappa, Prasanna D.; H. G., Gowtham; K. P., Chandana; Natarajamurthy, Shilpa; K., Nataraj; Pradeep, Sushma; Shivamallu, Chandan; Elossaily, Gehan M.; Achar, Raghu Ram; Silina, Ekaterina; Stupin, Victor; Manturova, Natalia; et al. (Frontiers in Chemistry, 2024)
Chromobacterium violaceum, an opportunistic human pathogenic bacterium, exhibits resistance to conventional antibiotics by exploiting its quorum sensing mechanism to regulate virulence factor expression. In light of this, disrupting the quorum sensing mechanism presents a promising avenue for treating infections caused by this pathogen. The study focused on using the cytoplasmic quorum sensing receptor CviR from C. violaceum as a model target to identify novel quorum sensing inhibitors from Picrasma quassioides through in silico computational approaches. Molecular docking analyses unveiled that several phytochemicals derived from P. quassioides exhibit the potential to inhibit quorum sensing by binding to CviR protein. Notably, the compounds such as Quassidine I (-8.8 kcal/mol), Quassidine J (-8.8 kcal/mol), Kumudine B (-9.1 kcal/mol) and Picrasamide A (-8.9 kcal/mol) exhibited high docking scores, indicating strong binding affinity to the CviR protein. The native ligand C6-HSL (N-hexanoyl-L-homoserine lactone) as a positive control/ co-crystal inhibitor also demonstrated a significant binding energy of -7.7 kcal/mol. The molecular dynamics (MD) simulation for 200 ns showed the thermodynamic stability and binding affinity refinement of the top-ranked CviR inhibitor (Kumudine B) with its stable binding and minor fluctuations compared to positive control (C6-HSL). Pharmacokinetic predictions indicated that Kumudine B possesses favourable drug-like properties, which suggest its potential as a drug candidate. The study highlight Kumudine B as a potential agent for inhibiting the CviR protein in C. violaceum. The comprehensive evaluation of Kumudine B provides valuable insights into its pharmacological profiles, facilitating its assessment for diverse therapeutic applications and guiding future research activities, particularly as antibacterial agents for clinical drug development.